Dihydroartemisinin Sensitizes Mutant p53 (R248Q)-Expressing Hepatocellular Carcinoma Cells to Doxorubicin by Inhibiting P-gp Expression. (31st December 2019) - Yang, Yue; He, Jianxin; Chen, Jing; Lin, Li; Liu, Yongqi; Zhou, Cunmin; Su, Yun; Wei, Hulai
Abstract : Mutant p53 (R248Q) induces doxorubicin (ADM) resistance in hepatocellular carcinoma (HCC). Dihydroartemisinin (DHA) can synergistically enhance anticancer effect of many chemotherapeutic agents. However, whether DHA could increase therapeutic efficacy of ADM in p53 (R248Q)-expressing HCC cells remains unknown. In the present study, we established mutant p53 (R248Q)-expressing Hep3B cells to study the effect and mechanism of DHA on ADM resistance and the synergistic effect of DHA with ADM. We found that P-gp was highly expressed in p53 (R248Q)-expressing Hep3B cells. As a result, cells expressing p53 (R248Q) displayed higher cell viability and lower cell apoptosis level upon ADM treatment. Meanwhile, phosphorylation levels of ERK1/2 and p65 were elevated in p53 (R248Q)-expressing Hep3B cells. However, combination of DHA and ADM treatment decreased cell viability and elevated cell apoptosis level in p53 (R248Q)-expressing Hep3B cells. Molecular dynamics simulations showed that DHA had the potential to bind with mutant p53 (R248Q) protein. Furthermore, DHA treatment decreased P-gp expression and inhibited phosphorylation levels of ERK1/2 and p65 in p53 (R248Q)-expressing Hep3B cells. Finally, DHA treatment could significantly reduce ADM efflux in p53 (R248Q)-expressing cells. Our results indicate that DHA could decrease P-gp expression via inhibiting the p53 (R248Q)-ERK1/2-NF- κ B signaling pathway, which eventually confers sensitization of p53 (R248Q)-expressing HCC cells to ADM. Our study provides evidence for the potential application of DHA and ADM combination in treatment of mutant p53 (R248Q)-harbored HCC.